Cardioprotective Effect of Nec-1 in Rats Subjected to MI/R: Downregulation of Autophagy-Like Cell Death - Liang Wang; Xuebai Lv; Jue Tian; Xiaoliang Wang; Ye Wu; Hui Rong Liu (Cardiovascular Therapeutics)
Objective. Necrostatin-1 (Nec-1), an inhibitor of necroptosis, has been reported to protect against myocardial ischemia-reperfusion (MI/R) injury. However, the contribution of the potential antinecroptotic effect of Nec-1 on its infarct limitation and cardiac function improvement effects after MI/R has not been investigated. Methods. The present study investigated the effect of Nec-1 on myocardial infarct size, necroptosis, and cardiac functional recovery in rats subjected to myocardial ischemia-reperfusion (MI/R 30 min/12, 24, 48, and 72 h). Results. The study showed that Nec-1 might reduce myocardial cell death and maintain myoarchitectonic integrity, consequently inhibiting the reactive fibrosis process in rats in myocardial ischemia/late reperfusion. Moreover, the administration of Nec-1 (0.6 mg/kg) at the onset of reperfusion significantly reduced the release of creatine kinase and downregulation of autophagy within 24 h after reperfusion, and there was a significantly positive correlation between them. Conclusion. These results suggest that antinecroptosis treatment may improve the clinical outcomes of patients with ischemic heart disease.